All trust is local: Sustainable development, trust in government and legitimacy in northern mining projects. (March 2021) - Poelzer, Gregory; Yu, Stan
Abstract: Gaining and maintaining legitimacy serves as one of the central goals for public officials for the sake of efficacy. Operating in a legitimacy deficit raises both political and economic costs as citizens lose trust in public institutions and processes hit delays and policy is ignored. For administrators tasked with resource extraction, strong incentives exist to improve the efficiency and effectiveness of their activities. To do this, understanding the citizens directly affected by resource development – their values and beliefs on sustainability – aids government in accomplishing its goals with lower costs. The greater the congruence between government and citizens perspectives, the greater the legitimacy. Norrbotten and Västerbotten, Sweden and Saskatchewan, Canada serve as the two cases in this paper. Both jurisdictions have established mining operations and, in the international context, strong regulatory frameworks. Further, during the mineral price boom, both regions saw increased foreign investment and new mine applications. Using survey data that focused on the perspective and values of residents living near potential mining operations, we look at the connection between trust in government and the acceptability of mining. Our findings indicate that trust in government holds the potential to overcome differences in values on sustainability; important for the on-going contentious debates on resource development. Highlights: General trust is not a predictor for acceptance of mining. Trust in sub-national government is a predictor of acceptance for mining operations. In some cases, trust in government can shift value differences to accept mining activities.